KAJIAN HUKUM ISLAM TERHADAP HAK MEREK SEBAGAI OBYEK DALAM PERJANJIAN RAHN - Hidayah, Khoirul (Fakultas Syariah, 2014)
Trademark right is industry property right that can to be company reputation and can protect the consumen from infringement. Trademark has economic value more than the other company assets.The fenomena about syariah economic in Islamic finance in Indonesia had to be interesting topic to study about trademark right as the object in rahn contract. The private law of Indonesia had explain that trademark right is the immovable intangible object. Trademark right can move to the other people. It can be sold and be inherited, hibah, and contract.Â In Islamic law studies, Ulama Hanafiah explain that the trademark as marhun, because it fulfill the requirement of rahn contract. MUI explain too about trademark in fatwa MUI in 2005. It explain that the trademark isÂ huquq maliyah (property right)and it protect by the law.